2019
DOI: 10.1186/s40463-019-0354-7
|View full text |Cite
|
Sign up to set email alerts
|

The middle fossa approach with self-drilling screws: a novel technique for BONEBRIDGE implantation

Abstract: Background Bone conduction implants can be used in the treatment of conductive or mixed hearing loss. The BONEBRIDGE bone conduction implant (BB-BCI) is an active, transcutaneous device. BB-BCI implantation can be performed through either the transmastoid or retrosigmoid approach with their respective limitations. Here, we present a third, novel approach for BB-BCI implantation. Objective Describe the detailed surgical technique of BB-BCI implantation through a middle f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 22 publications
(30 reference statements)
1
26
0
1
Order By: Relevance
“…The BB-BCI is the first active, transcutaneous BCI and multiple studies have shown it to be an effective device to treat hearing loss in patients with mixed or conductive hearing loss [10][11][12][13][14][15]. The BB-BCI can be implanted under a variety of surgical techniques, with the implant housed in either the TM or RF, and recently the MF location.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The BB-BCI is the first active, transcutaneous BCI and multiple studies have shown it to be an effective device to treat hearing loss in patients with mixed or conductive hearing loss [10][11][12][13][14][15]. The BB-BCI can be implanted under a variety of surgical techniques, with the implant housed in either the TM or RF, and recently the MF location.…”
Section: Discussionmentioning
confidence: 99%
“…The MF location is associated with improvements such as reduced operating time and a smaller skin incision [1]. The MF approach was first performed at London Health Sciences Centre (LHSC), London, ON, Canada in 2013 [10] with favorable surgical results reported with a follow-up of up to 6 years [1]. Since then, other groups have also used the MF approach with or without self-drilling screws with clinical success [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For patients with a bone thickness of less than 8.7 mm or other abnormal temporal bone structure, the Lifts system can help avoid excessive pressure on the dura or sigmoid sinus. Dedicated BB Lifts have been developed by MED-EL and are available in 1, 2, 3, and 4-mm sizes [ 18 ]. The use of Lifts allows implantation in younger children, and facilitates implantation in difficult cases [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%